O PROGRAMA DE EDUCAÇÃO TUTORIAL (PET) NA PERCEPÇÃO DE EGRESSOS DO GRUPO PET/EDUCAÇÃO FÍSICA DA UFMS: uma análise narrativa - MATHEUS BEZERRA DE SOUZA (2025)
The study focuses on the Tutorial Education Program (PET), a public policy that has been developed over the years in Brazilian undergraduate courses with the aim of contributing to the formation of researchers and professionals of excellence. The objective of the research is to analyze the relationships that may be established between participation in PET during undergraduate studies and the qualification of participants as researchers and future professionals. The research is guided by the following questions: from the perspective of PET participants – as they self-identify, the students from the Physical Education course at the Faculty of Education (Faed) of the Federal University of Mato Grosso do Sul (UFMS) – did the program contribute to their “excellent” formation? For students and alumni, is there a correlation between participation in PET and the quality of their academic and professional training? To address these questions, the theoretical framework is based on life history and formation studies, drawing from authors such as Cristine Delory-Momberger, Maria da Conceição Passeggi, Elizeu Clementino de Souza, and António Nóvoa, among others. Methodologically, the study involved literature review for theoretical foundation, state of the art to map academic production on PET, document analysis using sources such as reports and announcements related to the program at UFMS, questionnaires for active and alumni participants, and narrative interviews with alumni from the Physical Education/PET program at Faed/UFMS. The results indicate that PET was initially designed for a select target audience, aiming to form an intellectual elite focused on entry into postgraduate studies. However, for the interviewees, who came from working-class backgrounds, PET did not prove to be a decisive factor for entering postgraduate programs. From the alumni’s perspective, the policy made significant contributions to their academic and professional training by developing practical, technical, and social skills. However, all of these characteristics bring their own problems and challenges, such as time commitment, overload, lack of depth in activities, expectations, and internal conflicts. Based on these results, we conclude that PET is an educational public policy with significant contributions to participants’ formation, enabling the exploration of various skills and knowledge in teaching, research, and outreach. However, it also presents challenges and contradictions, such as participant overload, the demands placed, and the shallow treatment of the themes, which should be explored and further.